2003
DOI: 10.1507/endocrj.50.45
|View full text |Cite
|
Sign up to set email alerts
|

Practical Treatment with Minimum Maintenance Dose of Anti-Thyroid Drugs for Prediction of Remission in Graves' Disease.

Abstract: Although many researchers have reported clinical and laboratory parameters for prediction of remission in Graves' disease during or after anti-thyroid drug therapy, there is no reliable one to assure the complete remission. We prospectively examined a practical therapy with minimum maintenance dose of anti-thyroid drugs for prediction of remission in Graves' disease. Fifty-seven patients with Graves' disease were treated with anti-thyroid drugs at the initial dose of 30 mg/day of methimazole (MMI) or 300 mg/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
3
21
1
1
Order By: Relevance
“…It is worth noting that this dose of PTU is in the range of the minimum maintenance dose recently proposed for maintaining euthyroid status in Graves' disease (Kashiwai et al 2003). In these conditions, lower proliferative responses to T-and B-selective mitogens were found compared with euthyroid control mice.…”
Section: Discussionmentioning
confidence: 83%
“…It is worth noting that this dose of PTU is in the range of the minimum maintenance dose recently proposed for maintaining euthyroid status in Graves' disease (Kashiwai et al 2003). In these conditions, lower proliferative responses to T-and B-selective mitogens were found compared with euthyroid control mice.…”
Section: Discussionmentioning
confidence: 83%
“…One patient (2 %) in our study had transient unilateral vocal cord palsy detected by the fiberoptic laryngoscope, but without evident impairment of the voice. With regard to the control group, in addition to the wellknown side effects and recurrences following medical therapy [22,23], the most frequent problems that persisted despite anti-thyroid drug treatment concerned clinical manifestations (gastrointestinal, cardiovascular and muscular alterations), and also alterations in physical appearance, neurovegetative and psychological systems (anxiety, insomnia, depression and stress) and social disorders. Some improvement was observed in body weight and hormonal values at the beginning of therapy; although worsened ocular pressures, exophthalmos and migraine were also observed (final results summarized in Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…That is, these assays could detect TRAb even in some Graves' patients during clinical remission after antithyroid drug (ATD) treatment, so that physicians are encountering difficulties when judging the timing of drug cessation based upon the TRAb results. Many investigators reported difficulty in the prediction of clinical remission or relapse using TRAb results [5,[10][11][12][13][14], and some have already tried to set up elevated cut-off points based on retrospective analyses of their Graves' patients [15][16][17].…”
mentioning
confidence: 99%